Something's wrong! : a bear, a hare, and some underwear - John, Jory; Kraan, Erin (New York : Farrar Straus Giroux, 2021)
Jeff the bear is sure he has forgotten something when he sets out from home, but none of the animals he meets initially inform him that he is only wearing his underwear, until he reaches his friend Anders the hare--who quickly thinks of a way to avoid embarrassing Jeff, by starting a fashion trend.
Keywords: Bears -- Juvenile fiction; Hares -- Juvenile fiction; Animals -- Juvenile fiction; Embarrassment -- Juvenile fiction; Friendship -- Juvenile fiction; Humorous fiction; Picture books